Oral health status of children with type 1 diabetes: a comparative study - Ismail, Ahmad Faisal; McGrath, Colman Patrick; Yiu, Cynthia (De Gruyter, 2017)
Background: The aim of this study was to compare the oral health status of children with type 1 diabetes and healthy controls. Methods: This comparative study involved 64 children, 32 children with type 1 diabetes and 32 age- and gendermatched controls. Oral health examination was conducted using WHO criteria. Dental caries experience was recorded using DMFT/dmft index and periodontal parameters were assessed using plaque, gingivitis, gingival bleeding and calculus indexes. Dental caries and periodontal parameters between the two groups were compared using the Mann-Whitney U-test. Results: Children with diabetes exhibited significantly greater plaque deposits (p = 0.01) and a higher mean plaque index (p < 0.01), when compared to healthy subjects. No significant difference in DMFT and dmft scores, mean bleeding index, calculus index and gingival index was found between the two groups. Conclusions: Children with type 1 diabetes had a poor oral health status with greater plaque accumulation than children without diabetes.